DESIGN OF ACCOUNTING RECORDING SYSTEM AND FINANCIAL REPORTING ON PT PERMAI SOLUSI EKSPRESS - Vinnie Chelencia; Iskandar Itan (ConCEPt - Conference on Community Engagement Project, 2022)
This activity aims to design an accounting system to record transactions and prepare financial reporting that will make it easier for business owners to make good financial statements. Previously transactions were only recorded manually with Microsoft Excel so that human errors are vulnerable in recording. As a solution, a simple and easy accounting recording system is designed to produce correct and accurate records from September 2021 to December 2021. The object of this activity is PT Permai Solusi Ekspress which is engaged in the installation and repair of heavy equipment/freight equipment such as elevators, escalators, and travelators. The method used is to make observations to obtain the necessary information and discuss with business owners about the system needed. The output of this activity is an accounting recording system designed with Microsoft Access and should be implemented to make it easier to make financial statements. After the accounting recording system is implemented, the process of recording becomes more practical, receipts and expenses are recorded accurately, and helps with decision making regarding financial information. Next community services are suggested to create a website based application so that recording transcation and financial information can be access anytime.